2016
DOI: 10.7589/2015-11-317
|View full text |Cite
|
Sign up to set email alerts
|

HELMINTH INFECTIONS IN NORTHERN BOBWHITES (COLINUS VIRGINIANUS) FROM A LEGACY LANDSCAPE IN TEXAS, USA

Abstract: The Northern Bobwhite ( Colinus virginianus ) has declined across its range. The primary cause of this decline is thought to be habitat loss and fragmentation. However, there is speculation that factors such as parasites may play a role. South Texas recently was designated a Legacy Landscape of National Significance for Northern Bobwhite Conservation and is a region with some of the highest bobwhite densities in the US. Limited studies on bobwhite parasites have been conducted in this crucial landscape. We doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 10 publications
6
34
1
Order By: Relevance
“…Concerns have been raised regarding negative impacts of A. pennula on bobwhites (Dunham et al , 2017). Similar to Olsen & Fedynich (2016), we observed distension in the terminal portions of the ceca when A. pennula infections were high (>300 worms). Nematodes may take advantage of regulatory molecules to evade the host immune system (Maizels et al , 2001), creating tolerance and allowing infections to persist.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Concerns have been raised regarding negative impacts of A. pennula on bobwhites (Dunham et al , 2017). Similar to Olsen & Fedynich (2016), we observed distension in the terminal portions of the ceca when A. pennula infections were high (>300 worms). Nematodes may take advantage of regulatory molecules to evade the host immune system (Maizels et al , 2001), creating tolerance and allowing infections to persist.…”
Section: Discussionsupporting
confidence: 90%
“…Species composition also differed between the component communities in the southeastern U.S. and our study. Aulonocephalus pennula was the numerically dominant species in our study and is a common (>75% prevalence) and abundant species found in quail species from Texas (Webster & Addis, 1945; Lehmann, 1984; Landgrebe et al , 2007; Bedford, 2015; Olsen & Fedynich, 2016; Villarreal et al , 2016) and New Mexico (Campbell & Lee, 1953), but is not found in bobwhites from Florida, Georgia (Kellogg & Prestwood, 1968), North Carolina (Cram et al , 1931; Blakeney & Dimmick, 1971) or Kansas (Williams et al , 2004). Component communities in the southeastern U.S. also consist of more monoxenous nematode species (range: 2–4), which occurred in high intensities (>30; Moore et al , 1986; Moore & Simberloff, 1990; Davidson et al , 1991).…”
Section: Discussionmentioning
confidence: 62%
“…Similar helminth community structure and patterns found in our study were reported in scaled quail by Landgrebe et al . (2007), in northern bobwhites ( Colinus virginianus ) within South Texas (Olsen & Fedynich, 2016), and except for species richness, in northern bobwhites within the Rolling Plains of Texas and western Oklahoma (species richness = 13; Bruno et al ., 2018). These studies found most if not all species were heteroxenous, one species ( A. pennula ) was highly prevalent and abundant, and most of the remaining species rarely occurred and contributed few individuals to the helminth component community.…”
Section: Discussionmentioning
confidence: 99%
“…pennula and O . petrowi to be ubiquitous in quail throughout the region ( Dunham et al, 2016a ; Olsen and Fedynich, 2016 ). In subsequent studies, Bruno et al (2019b) found 40% of bobwhite sampled from 2011 to 2013 to be infected with O .…”
Section: Using the Woe Framework To Investigate The Role Of Parasitesmentioning
confidence: 99%